Tolerance to arsenic contaminant among multidrug-resistant and copper-tolerant Salmonella successful clones is associated with diverse ars operons and genetic contexts - Mourão, Joana (2021)
Emergence and expansion of frequent multidrug-resistant (MDR) major Salmonella clones/serotypes has been a significant threat in the last years. Metal compounds, such as copper, commonly used in animal-production settings, have been pointed out as possible contributors for the selection of such strains/clones.